DIACHRONY OF ACCOUNTING AND AUDITING TERMS IN ENGLISH AND UZBEK LANGUAGES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, we will consider the origin of the field of accounting and auditing in English and Uzbek, as well as the history of accounting terms, the opinions of scientists, and the etymology of this field.